2006
DOI: 10.1037/0278-6133.25.5.658
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent girls' and boys' weight-related health behaviors and cognitions: Associations with reputation- and preference-based peer status.

Abstract: In this study, the authors examined associations between preference- and reputation-based peer status and weight-related behaviors and cognitions for both adolescent boys and girls. Sociometric measures of peer like-ability and peer-perceived popularity, as well as self-reported measures of body size, dieting behavior, and weight-related cognitions were collected from a sample of 441 adolescents in Grades 11 and 12. Results revealed weight-related cognitions for girls (concerning obesity) and boys (concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…Given their normative nature, participation in these activities does not necessarily lead to elevated standing or increased social visibility among peers. As one study [24] found that popularity was associated with body size and dieting behaviours for students in grades 11 and 12, it would be beneficial to explore the less normative body image-related risk-taking behaviours, such as fasting or self-induced vomiting for those seeking thinness, and excessive weight-lifting and steroid use for those seeking muscularity, in future studies, particularly with older adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given their normative nature, participation in these activities does not necessarily lead to elevated standing or increased social visibility among peers. As one study [24] found that popularity was associated with body size and dieting behaviours for students in grades 11 and 12, it would be beneficial to explore the less normative body image-related risk-taking behaviours, such as fasting or self-induced vomiting for those seeking thinness, and excessive weight-lifting and steroid use for those seeking muscularity, in future studies, particularly with older adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study investigated popularity along with discrepancies between perceived actual body size and ideal body size in grade 11 and 12 students [24]. This study found that higher popularity was significantly associated with self-reported muscular body shapes for boys, and that lower popularity was associated with self-reported larger body shapes for girls [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although media sources are a strong influence, research suggests that adolescents rely greatly on their friends when it comes to the development of body image and weight-related behaviors (Wang, Houshyar, & Prinstein, 2006). Shomaker andFurman (2009, 2010) found that interpersonal pressure from parents, romantic partners and friends are important sources of influence on attitudes or behaviors towards muscle gaining and on anorexic-like and bulimic-like behaviors such as drive for thinness, excessive dieting, excessive exercising, purging and binging.…”
Section: Introductionmentioning
confidence: 99%
“…Peer victimisation is very psychologically damaging to young children, as at this age, they need much support from their peers (Kawabata & Crick, 2011). Victimisation may include name-calling, spreading rumours, bullying and even loss of friendship due to embarrassment (Wang, Houshyar, & Prinstein, 2006).…”
Section: Critiques and Barriers To School-based Obesity Preventionmentioning
confidence: 99%